2012
DOI: 10.1021/pr201223p
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Dependent Metabolic Signatures Associated with Nonalcoholic Fatty Liver Disease Progression

Abstract: Our understanding of the mechanisms by which nonalcoholic fatty liver disease (NAFLD) progresses from simple steatosis to steatohepatitis (NASH) is still very limited. Despite the growing number of studies linking the disease with altered serum metabolite levels, an obstacle to the development of metabolome-based NAFLD predictors has been the lack of large cohort data from biopsy-proven patients matched for key metabolic features such as obesity. We studied 467 biopsied individuals with normal liver histology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(197 citation statements)
references
References 44 publications
7
184
1
3
Order By: Relevance
“…This BMI‐dependent serum lipidomic test measures the probability of a certain sample to belong to one of these three groups: NL, NAFL, and NASH. In that previous work, a total of 467 biopsy‐proven samples, classified as NL, NAFL, or NASH, were analyzed using three different metabolic UPLC‐MS platforms that measured 540 different lipids and amino acids 19. Taking this work as a reference point, the next steps were conducted to reduce the complexity of the test by means of reducing the number of metabolites that needed to be measured as well as the required analytical platforms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This BMI‐dependent serum lipidomic test measures the probability of a certain sample to belong to one of these three groups: NL, NAFL, and NASH. In that previous work, a total of 467 biopsy‐proven samples, classified as NL, NAFL, or NASH, were analyzed using three different metabolic UPLC‐MS platforms that measured 540 different lipids and amino acids 19. Taking this work as a reference point, the next steps were conducted to reduce the complexity of the test by means of reducing the number of metabolites that needed to be measured as well as the required analytical platforms.…”
Section: Resultsmentioning
confidence: 99%
“…MS lipidomics is a high‐throughput technology that can measure simultaneously hundreds of different lipid classes and molecular species in a small volume of serum 37, 38, 39, 40. We first demonstrated this concept by showing that a panel of 540 lipids could differentiate NAFLD from NL and NASH from NAFL 19. We also observed that categorizing patients by their BMI improved the power of the classification algorithm 41.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Metabolic profiles of urinary EVs were semi-quantified using four UHPLC-MS based analytical platforms as previously described [17,18]. Methanol was first added to urinary EV preparations, and after brief vortex, chloroform was added.…”
Section: Metabolite Extraction and Uhplc-ms Analysismentioning
confidence: 99%
“…Chromatographic separation and mass spectrometric detection conditions employed were previously described [17,18]. The overall quality of the analysis procedure was monitored using six repeat injections of a pooled sample, considered as the quality control sample.…”
Section: Metabolite Extraction and Uhplc-ms Analysismentioning
confidence: 99%